APLIKATISI MODERASI DALAM INTERAKSI MUSLIM DAN NON-MUSLIM PERSPEKTIF TAFSIR NABAWI - Muhammad Alan Juhri (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
The phenomenon of hostility, blaming each other, and justifying their own groups is alarming and threatens existing social integration. Religion actually condemns the attitude of vigilante, believing groups and their religion is right, and other religions are false religions. Islam itself has rules in the Qur'an and Sunnah. The Prophet Muhammad always campaigned for rahmatal lil alamin Islam, where the sentence has the function of Islam as a religion of protection, peace, prosperity, and without discrimination. This has been practiced by the Prophet according to Surah al-Mumtahanah verses 8-9, Allah did not forbid the Prophet to do good and do justice to non-Muslims who did not hostile him. Furthermore, using descriptive-analytical methods, in this paper the author analyzes the traditions of the Prophet that explain the verses of the Qur’an regarding Muslim and non-Muslim relations, so that later it can become one of the efforts in realizing tolerance between people religious.